Anuê Jaci: foreign policy and indigenous peoples facing conservative inflection and bolsonarism - Santos, César (Faculdade de Ciências e Letras - Unesp - Araraquara., 2020)
On the eve of the bicentenary of Brazil’s Independence from Portugal (1822- 2022), Jair Messias Bolsonaro’s rise to the Presidency of the Republic challenges the Brazilian people to witness the return of Christian ideology, from the XVI and XVII, as the orientation of the Brazilian Government in the XXI century. In the Ministry of Foreign Affairs (MRE), the body responsible for promoting and defending Brazil’s interests abroad, the appointment of Ambassador Ernesto Araújo as Chancellor brought the Christian ideology to the epicentre of the orientation of Brazil’s foreign policy. In this same context, the number of assassinations of indigenous leaders in Brazil has configured a state of war, fuelled, among other reasons, by the absence of the demarcation of indigenous lands provided for in the 1988 Federal Constitution. In 2019, the Articulation of Indigenous Peoples of Brazil (APIB) held the “Indigenous Blood: not one drop more” in several countries on the European continent to denounce the genocidal practice of the Brazilian government. It is not common to establish a direct relationship between foreign policy and indigenous peoples. This article is part of a theoretical study, still preliminary, that aims to contribute to the expansion of the field of empirical observation in foreign policy analysis (APE) and points to the need to build an indigenist paradigm to the Brazilian foreign policy in light of the paradigmatic model proposed by Professor Amado Luiz Cervo. This involves the inclusion of the indigenous component in the formulation of national interest after the promulgation of the Federal Constitution of 1988, as well as the validity of Convention 169, of the International Labour Organisation (ILO), concerning indigenous and tribal peoples. It is hoped that the inclusion of the indigenous component can contribute to other analyses of the formulation of national interest, not only in Brazil, but also in the other national states that are signatories of Convention 169/OIT.